MELTING OF AMPHIBOLE-BEARING WEHRLITES: AN EXPERIMENTAL STUDY ON THE ORIGIN OF ULTRA-CALCIC NEPHELINE-NORMATIVE MELTS - Médard E.; Schiano P.; Schmidt M.W.; Ottolini L. (My University, 2006)
Olivine + clinopyroxene ± amphibole cumulates have been widely documented in island arc settings and may constitute a significant portion of the lowermost arc crust. Because of the low melting temperature of amphibole (1100°C), such cumulates could melt during intrusion of primary mantle magmas. We have experimentally (piston-cylinder, 0.5-1.0GPa, 1200-1350°C, Pt-graphite capsules) investigated the melting behaviour of a model amphibole-olivine-clinopyroxene rock, to assess the possible role of such cumulates in island arc magma genesis. Initial melts are controlled by pargasitic amphibole breakdown, are strongly nepheline-normative and are Al2O3-rich. With increasing melt fraction (T> 1190°C at 1.0GPa), the melts become ultra-calcic while remaining strongly nepheline-normative, and are saturated with olivine and clinopyroxene. The experimental melts have strong compositional similarities to natural nepheline-normative ultra-calcic melt inclusions and lavas exclusively found in arc settings. The experimentally derived phase relations show that such natural melt compositions originate by melting according to the reaction amphibole + clinopyroxene = melt + olivine in the arc crust. Pargasitic amphibole is the key phase in this process, as it lowers melting temperatures and imposes the nepheline-normative signature. Ultra-calcic nepheline-normative melt inclusions are tracers of magma-rock interaction (assimilative recycling) in the arc crust. © The Author 2005. Published by the Oxford University Press. All rights reserved.
Keywords: EXPERIMENTAL MELTING; SUBDUCTION ZONE; ULTRA-CALCIC MELTS; WEHRLITE